2012 : The crystal skull - Scott, Manda (London : Bantam Books, 2009)
Stella Cody, who has found the last blue crystal skull needed to prevent the destruction of the world, attempts to decode the previous Keeper's coded writings as time runs short and people try to kill her.
Includes bibliographical references (p. [450]-451).
Adult
Keywords: End of the world -- Fiction; Treasure troves -- Fiction; Adventure fiction; Buried treasure -- Fiction; England -- Fiction; Suspense fiction